Health research protocols: a template for empirical bioethics and other investigations - Henri-Corto Stoeklé; Christian Hervé (Health Research Policy and Systems, 2025)
Abstract We have formalized a protocol template suitable for all types of humanities and social sciences investigations in the domain of health, including empirical bioethics in particular. To achieve this, we revisited the protocol template proposed by O’Brien et al. in Academic Medicine in 2014, better known as the “Standards for Reporting Qualitative Research (SRQR)”. We reorganized, fused and/or renamed several of the sections, and partly or entirely rewrote several of the corresponding instructions. This made it possible to overcome the limitation of the initial protocol to qualitative approaches, and to render the resulting template equally suitable for quantitative and mixed approaches, and/or other approaches. This new protocol template should be seen as a highly adaptable base.